Substantiating technological factors for preparing fermented milk-containing products with a combined composition of raw materials with a long storage period - Andreus, Svitlana; Romanchuk, Iryna; Rudakova, Tetіana; Narizhnyy, Sergiy (Eastern-European Journal of Enterprise Technologies, 2024)
This paper substantiates and defines the technological parameters for obtaining stable emulsions when making fermented milk-containing products. The object of research was the modes of mechanical and heat treatment of mixtures with a combined composition of raw materials based on dairy and vegetable fats. The task to be solved was to obtain stable emulsions by two-stage homogenization of the cream-vegetable mixture and the heat treatment temperature of the fermented cream-vegetable mixture with a combined composition of raw materials with a fat content of 10 % and 15 %. It is shown that during the homogenization of a cream-vegetable mixture with a mass fraction of fat of 10 %, the pressure in the first stage should be 10.0–12.0 MPa, in the second – 2.5–3.0 MPa; for a cream-vegetable mixture with a mass fraction of fat of 15 %, the pressure in the first stage is 8.0–10.0 MPa, in the second – 2.5–3.0 MPa. Modes of thermomechanical processing of the fermented cream-vegetable mixture at temperatures of 65±2 and 70±2 °C to ensure the microbiological stability of the milk-containing product during storage have been substantiated. A stabilizing system based on milk proteins has been selected. It was established that in order to improve the consistency, increase heat resistance, and avoid foaming of the finished product, it is necessary to perform thermomechanical processing of the fermented cream-vegetable mixture with a fat content of 10 % and 15 % at temperatures of 70±2 °С and 65±2 °С, respectively, and mass fraction stabilizer – 0.5 % and 0.15 %, respectively. The research data do not always coincide with previously established patterns, which is due to the difference in the chemical composition of the studied food systems, as well as the methods of their preparation and use. The results of the work could be used in the technology of milk-containing products with a combined fat composition